2013
DOI: 10.1093/intimm/dxt029
|View full text |Cite
|
Sign up to set email alerts
|

Application of an M-cell-targeting ligand for oral vaccination induces efficient systemic and mucosal immune responses against a viral antigen

Abstract: Oral mucosal vaccination is an alternative method to overcome the pitfalls of current injection-based vaccines, such as pain and high cost of vaccination. It is a feasible and economic vaccine application, especially in developing countries. However, achieving effective antigen delivery into mucosal lymphoid organs and efficient immune stimulation are prerequisites to successful oral mucosal vaccination. One promising approach for oral mucosal vaccine development is exploring the potential of M cells via M-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Resulting antibodies induced by the ligand-conjugated EDIII antigen show effective virus- neutralizing activity. Taken together, these observations confirm that the M-cell-targeting strategy using Co1 ligand as a mucosal adjuvant may be a beneficial tool in the pursuit of effective vaccines for pathogenic DENV antigen [ 23 ].…”
Section: Introductionsupporting
confidence: 58%
“…Resulting antibodies induced by the ligand-conjugated EDIII antigen show effective virus- neutralizing activity. Taken together, these observations confirm that the M-cell-targeting strategy using Co1 ligand as a mucosal adjuvant may be a beneficial tool in the pursuit of effective vaccines for pathogenic DENV antigen [ 23 ].…”
Section: Introductionsupporting
confidence: 58%
“…Efficient antigen delivery into PPs was observed and the antibodies induced by the Co1-ligand-conjugated EDIII antigen showed effective virus-neutralizing activity. 65 Taken together, these results reveal that M-cell-targeting ligands with adjuvant activity can be designed to exploit our knowledge of receptors expressed on the apical surface of M cells involved in pathogen invasion.…”
Section: Co1 Ligandmentioning
confidence: 77%
“…[63][64][65] Co1 ligand promotes the uptake of fused antigen and enhances the immune response against the fused antigen, indicating that Co1 could be used as an adjuvant for targeted antigen delivery into the mucosal immune system to enhance immune induction. 64 Another promising approach used Co1 ligand to induce specific immune responses against a pathogenic viral antigen, EDIII of DENV.…”
Section: Co1 Ligandmentioning
confidence: 99%
“…In previous studies, it has been suggested that receptors expressed in the apical area of M cells could be utilized as M cell-targeting receptors for mucosal vaccine antigens ( 16 ). Consequently, we speculated that P2X 7 R might also serve as an M cell-targeting receptor for delivery of mucosal vaccine antigens.…”
Section: Resultsmentioning
confidence: 99%